Clinical Types and Infective Pattern of Pyogenic Neck Abscess in Diabetic Patients - Md Shariful Alam,; Khan Md Nazmus Saqeb,; Md Monwar Hossain,; Mahmima Islam Shikha, (Bangladesh Critical Care Journal, 2025)
Background: Complex anatomy of neck makes the diagnosis and treatment of the neck abscess challenging. Diabetic patients especially with poorly controlled are more susceptible for such infection and faces virulent pyogenic bacteria. The course of the disease may be more rapidly progressive and serious. Some fatal complications may occur like airway obstruction, pneumonia, lung abscess, mediastinitis etc. We aimed to detect the bacteria causing different clinical types of pyogenic neck abscess and their antimicrobial sensitivity in diabetic patients. Methods: It is a prospective observational type of study carried out in the Department of Otolaryngology and Head Neck Surgery of BIRDEM General Hospital, Dhaka from 1st December, 2019 to 31st May, 2020. Total 50 cases of diabetic patients having neck abscess were selected by purposive consecutive sampling. Then history taking, clinical examinations, relevant investigations along with antibiogram were done in all cases. Afterwards data were collected in a preformed data collection sheet. Then data were analysed with Statistical Package for the Social Sciences (SPSS) V 22.0. Results: Among the 50 cases 30 were male and 20 were female. Age ranges from 32 to 83 years and mean age was 55.28 years. The commonest symptom was neck swelling 47 (94%). Other symptoms were neck pain 46 (92%), fever 42 (84%), difficulty in swallowing 15 (30%), difficulty in mouth opening 14 (28%), toothache 7 (14%), H/O tooth extraction 6 (12%), H/O neck surgery 3 (6%) and respiratory difficulty 1 (2%). On clinical examination commonly 47 (94%) patients had neck swelling which was subsequently followed by pyrexia 36(72%), trismus 16 (32%), dental caries 14 (28%) and halitosis 13 (26%). Commonest aetiology was dental origin. Most common pyogenic abscesses were involved in the anterior triangle of the neck 15 (30%) followed by Ludwig’s angina 12 (24%), submandibular abscess 10 (20%), abscess in the posterior triangle 7 (14%), parotid abscess 4 (14%), retropharyngeal abscess 1 (2%) and parapharyngeal abscess 1 (2%). Bacteria isolated from pus culture revealed Klebsiella pneumoniae 23 (46%), Staphylococcus aureus 6 (12%), Pseudomonas 5 (10%), Acinetobacter 4 (08%), E.coli 1 (2%), Proteus 2 (4%), MRSA 1 (2%), Beta haemolytic streptococcus 1 (2%). All the organisms were mostly sensitive to Meropenem, Colistin, Netilmicin, Gentamicin, Amikacin, Piperacillin+Tazobactum. But Acinetobacter was highly sensitive to only Colistin. Conclusion: Neck abscess in diabetic patients occurred commonly in male with lower middle socio-economic class. The virulence of organism is more in case of uncontrolled diabetes. Abscess in the anterior triangle was the commonest type of neck abscess and Klebsiella pneumoniae was the most frequently isolated organism. Empirical antibiotic treatment must cover gram positive, gram negative and anaerobic pathogens. Early surgical intervention can reduce the complications. Bangladesh Crit Care J March 2025; 13 (1): 23-29